D. M. Ovsianyko-Kulikovsky as an Orthologist: the Cognitive-evolutionary Coverage - Sergiy Popov (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article is devoted to the cognitive-evolutionary coverage of D. M. Ovsianyko-Kulikovsky's beliefs as an orthologist who expressed his orthological convictions regarding the norms of syntactic agreement of adjectives with homogeneous noun phrases. The scholar categorically denied the possibility of such agreement in the plural, despite the fact that in the eighteenth century such agreement was already quite common in usage as a logical agreement of the plural adjective with more than one noun.